NOT ONE, BUT TWO WARS. ADRIANA DEVERNEUIL, FRANCE AND PERU (1870 AND 1879) - Rosario, Emilio (2015)
The item is a contrast between the Franco-Prussian War and the Pacific War, narrated from experienced by Adriana de Verneuil in the book Mi Manuel experiences will be performed. In this way we will know as the collection of quotas, women abuse and humiliation of civilians which I spank her homeland during the War of 1870; were reflected in the war of 1879, generating identification thereof by the Peruvian cause.